Next-Generation Wireless Networks - Naeem, Burhan (Journal of Computers and Intelligent Systems, 2024)
Next-generation wireless networks, commonly referred to as 5G and beyond (6G, 7G), are poised to revolutionize the way we communicate, connect, and interact in our increasingly digital world. With unprecedented speed, capacity, and reliability, these networks are expected to deliver ultra-low latency and support massive machine-to-machine communications, enabling a wide range of innovative applications and services. In this work, we offer a survey of the principal methods now in use and architectural principles driving the development of next-generation wireless networks. It explores deep into topics like millimeter-wave communication, huge MIMO systems, and network virtualization to explain their core ideas and principles. Potential advantages and disadvantages of such advanced networks are discussed. Topics covered include the introduction of Internet of Things (IoT) devices, the development of edge computing, and the requirement for increased security and privacy safeguards. Furthermore, this paper highlights ongoing research efforts and standardization activities in the field, aiming to ensure seamless interoperability and global deployment of next-generation wireless networks. As the demand for ubiquitous connectivity continues to escalate, the transition to next-generation wireless networks promises to reshape industries, empower smart cities, and unlock the full potential of emerging technologies such as autonomous vehicles, virtual reality, and artificial intelligence.